2015
DOI: 10.1063/1.4918652
|View full text |Cite
|
Sign up to set email alerts
|

High-performance giant magnetoresistive sensorics on flexible Si membranes

Abstract: We fabricate high-performance giant magnetoresistive (GMR) sensorics on Si wafers, which are subsequently thinned down to 100 mu m or 50 mu m to realize mechanically flexible sensing elements. The performance of the GMR sensors upon bending is determined by the thickness of the Si membrane. Thus, bending radii down to 15.5mm and 6.8mm are achieved for the devices on 100 mu m and 50 mu m Si supports, respectively. The GMR magnitude remains unchanged at the level of (15.3 +/- 0.4)% independent of the support thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…To improve adhesion and to protect the magnetic stack while lithographic processing, it was sandwiched with 2 nm thick Ta layers. Sputtering from the Ni 80 Fe 20 target material resulted in a composition shift in the resultant alloy film to Ni 81 Fe 19 with a non‐zero magnetostriction of this alloy . In particular, for Ni 81 Fe 19 thin films, increased values of the saturation magnetostriction, λ s , were attributed to interfacial effects…”
Section: Methodsmentioning
confidence: 99%
“…To improve adhesion and to protect the magnetic stack while lithographic processing, it was sandwiched with 2 nm thick Ta layers. Sputtering from the Ni 80 Fe 20 target material resulted in a composition shift in the resultant alloy film to Ni 81 Fe 19 with a non‐zero magnetostriction of this alloy . In particular, for Ni 81 Fe 19 thin films, increased values of the saturation magnetostriction, λ s , were attributed to interfacial effects…”
Section: Methodsmentioning
confidence: 99%
“…Conventional rigid semiconductor-based sensors with the typical thickness of about 400 µm cannot be used for these purposes calling for the development of flexible and thin sensors. Flexible and even stretchable magnetoelectronics relying on the giant magnetoresistance (GMR) effect in multilayers [4][5][6][7][8], spin valves [9,10], or magnetic tunnel junctions [11,12] are already established. However, these devices typically reveal a maximum sensitivity at several mT.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the performance of GMR multilayered magnetic sensors realized on thinned Si membranes was reported. 73 It was shown that the thinning down to 50 lm thickness of the Si support renders enough flexibility to attain bending radii down to 6.8 mm, keeping the GMR ratio of the sensors unchanged at a value of (15.3 6 0.4)%. Mechanical and magnetic stability has been proven with cyclic bending experiments.…”
Section: Further Development Directionsmentioning
confidence: 99%
“…Despite the manifold functionalities that are available for shapeable electronic systems, magnetic functionality ( Figure 1) was added to the family of flexible, [67][68][69][70][71][72][73] printable, [74][75][76] stretchable, 43,77,78 and even imperceptible 79 electronics very recently.…”
Section: A Magnetic Functionalities For Shapeable Electronicsmentioning
confidence: 99%